2012
DOI: 10.1007/s00403-012-1214-8
|View full text |Cite
|
Sign up to set email alerts
|

German S3-guidelines on the treatment of psoriasis vulgaris (short version)

Abstract: Psoriasis vulgaris is a common and often chronic inflammatory skin disease. The incidence of psoriasis in Western industrialized countries ranges from 1.5 to 2%. Patients afflicted with severe psoriasis vulgaris may experience a significant reduction in quality of life. Despite the large variety of treatment options available, patient surveys have revealed insufficient satisfaction with the efficacy of available treatments and a high rate of medication non-compliance (Richards et al. in J Am Acad Dermatol 41(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 206 publications
2
82
0
7
Order By: Relevance
“…Although many patients with mild‐to‐moderate psoriasis are treated with topical therapy alone,6, 7, 8 adherence remains a significant issue as the daily treatment regimen can be cumbersome and time consuming 9. Studies have shown that the type of topical vehicle used can impact on adherence;10, 11 patients prefer a vehicle that is simple and fast to apply, quickly absorbed and non‐greasy 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many patients with mild‐to‐moderate psoriasis are treated with topical therapy alone,6, 7, 8 adherence remains a significant issue as the daily treatment regimen can be cumbersome and time consuming 9. Studies have shown that the type of topical vehicle used can impact on adherence;10, 11 patients prefer a vehicle that is simple and fast to apply, quickly absorbed and non‐greasy 12…”
Section: Introductionmentioning
confidence: 99%
“…Topical formulations containing corticosteroids and/or vitamin D 3 analogues are recommended for treating psoriasis 7, 8, 13, 14, 15. The efficacy and safety of the fixed combination of calcipotriol 50 μg/g (Cal) and betamethasone 0.5 mg/g as dipropionate (BD) has been confirmed in long‐term trials 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Estes agentes devem ser aplicados nos dias de repouso da fototerapia, ou após a realização do tratamento para não interferirem com a penetração da radiação UV. 20 A aplicação tópica de tazaroteno em combinação com UVB de banda estreita ou PUVA pode aumentar a eficácia terapêu-tica, permitindo uma redução da dose cumulativa necessária à melhoria do quadro. Contudo, o uso deste retinóide tópico aumenta o risco de queimadura local, devendo ser ajustadas as doses de radiação utilizadas.…”
Section: Tópicosunclassified
“…Drugs that allow to treat many different clinical manifestations of PsO and/or PsA help to reduce the number of drugs a patient needs to take. This is of direct clinical relevance, as comorbidity and resulting comedication is a common problem in PsO patients and minimizing the likelihood for drug-drug interactions is therefore regarded as important [2,26] . Moreover, simplifying the treatment regimen is likely to increase patient adherence [29] .…”
Section: Management Of Psamentioning
confidence: 99%
“…The efficacy of DMARDs on skin and joint symptoms is quite diverse: while methotrexate is considered to be fairly effective on PsO [26] , leflunomide -which is regarded as an effective therapy for PsA -has shown insufficient efficacy on skin symptoms to warrant its use in dermatology [27] . Moreover, DMARDs have shown insufficient efficacy in certain common clinical manifestations of PsA, namely axial involvement, dactylitis and enthesitis [28] .…”
Section: Management Of Psamentioning
confidence: 99%